2009
DOI: 10.1159/000218711
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Associated with Complex Human Diseases Show Wide Variation across Multiple Populations

Abstract: Background: The wide use of genome wide association studies (GWAS) has led to the successful identification of multiple genetic susceptibility variants to several complex human diseases. Given the limited amount of data on genetic variation at these loci in populations of non-European origin, we investigated population variation among 11 population groups for loci showing strong and consistent association from GWAS with several complex human diseases. Methods: Data from the International HapMap Project Phase 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 30 publications
7
116
1
Order By: Relevance
“…It is therefore possible to speculate, on the basis of the high differentiation between the two examined samples, that these could have a role in the susceptibility to common complex diseases. 52,53 These results could have a predictive value for incoming association studies focused on multifactorial diseases in the same sub-populations.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is therefore possible to speculate, on the basis of the high differentiation between the two examined samples, that these could have a role in the susceptibility to common complex diseases. 52,53 These results could have a predictive value for incoming association studies focused on multifactorial diseases in the same sub-populations.…”
Section: Discussionmentioning
confidence: 82%
“…52 In fact, examination of allele frequencies in 11 HapMap phase III populations has demonstrated high levels of variation for the markers already associated with complex diseases and traits in genome-wide scans. 53 It is then plausible that a similar phenomenon could occur also in a limited geographical area such as Sardinia, especially according to the heterogeneity found among its examined groups.…”
Section: Discussionmentioning
confidence: 94%
“…Most of these GWAS have been conducted in populations of European ancestry. 3 Allele frequencies at loci showing strong and consistent association from GWAS with any of five common complex human conditions -type 2 diabetes, obesity, Crohn's disease, prostate cancer and breast cancer have shown wide variation across the 11 populations in the phase III of the International HapMap Project. 3 Another study of 25 single-nucleotide polymorphisms (SNPs), which show robust GWAS-derived associations with six complex human diseases (Crohn's disease, type 1 diabetes, type 2 diabetes, rheumatoid arthritis, coronary artery disease and obesity) using individuals from 53 populations worldwide resulted in substantial variation in risk allele frequencies among populations.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, one study has shown a wide variation in allele frequencies across different populations for the SNPs identified by GWAS for several complex diseases and traits. 141 A new risk allele for breast cancer was also identified by a GWAS carried out in a Chinese population and this was replicated in women of European ancestry. As in the T2D case, the risk allele has gone undetected by several European GWAS of breast cancer.…”
Section: Extending Gwas To Different Populationsmentioning
confidence: 81%